Assessment of the Auto-Oxidation Tendency and the Storage Effects on the Quality of Lignite in Oltenia Basin - MATEI, Oana-Raluca; TRAISTĂ, Camelia; TRAISTĂ, Eugen; SORIN, Radu (Studia Universitatis Babeș-Bolyai Chemia, 2024)
Coal auto-oxidation is an undesirable chemical phenomenon that occurs due to the interaction of coal with atmospheric oxygen, a phenomenon that takes place during the coal life cycle, from the extraction moment until it is used. Thus, it is imperative to understand this process not only for the prevention of coal autoignition in the mining industry, but also for the optimization of the coal storage. The aim of this work was to assess the chemical behavior such as the oxidation, self-heating, and auto-ignition characteristics of coal in Oltenia Basin, Romania during its storage period. The hydrogen peroxide oxidation testing was used to determine the auto-oxidation tendency of lignite, while for the monitoring of coal quality during the storage process, coal samples were taken from a coal stack after 0, 5, 10, 20 and 30 days of storage and analyzed regarding the moisture (39,71%), ash content (35.21 – 37,11%), calorific value (1940 – 1875 kcal/kg), and volatile compounds (36.71 – 37,27%). A good correlation between the autoxidation and the content of volatile matter was observed. Compared to the initial values measured in initial coal samples (day 0), the carbon content and the superior calorific value decreased, while the ash content increased after a period of 30 days of storage. Thus, it can be concluded that knowing the self-ignition characteristic of lignites is important both for managing coal stocks and for evaluating the impact that coal storage can have on the environment.